'Say on pay' regulations and director remuneration: evidence from the UK in the past two decades. Issue 2 (2nd July 2020) - Wu, Betty (H.T.); MacNeil, Iain; Chalaczkiewicz-Ladna, Katarzyna
ABSTRACT: The UK was the first country to introduce so-called 'say on pay' regulation in 2002, by providing shareholders with an advisory vote on the Directors' Remuneration Report. That approach recognised that disclosure alone was not an adequate regulatory response to the widening gap between directors' pay and company performance nor to the broader political concern over the implications of this trend for social solidarity. A second stage in the evolution of the regime began in 2013 when shareholders were granted a binding vote on remuneration policy. In this article we present the results of the first longitudinal survey of the entire phase of 'say on pay' regulation in the UK to date. We examine the link between each stage of 'say on pay' regulation and the level and growth of directors' remuneration. We conclude by linking our empirical evidence to broader developments in shareholder engagement with listed companies.